2013
DOI: 10.1039/c3dt50907a
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable two-phase procedure for V-catalyzed toluene oxidative bromination with H2O2–KBr

Abstract: A sustainable V(V) and Mo(VI) catalysed two-phase procedure for bromination of toluene under quite mild conditions is proposed; H 2 O 2 is the primary oxidant and KBr is the bromine source; metal precursors are commercially available salts. The reaction is efficient without any additional solvent. By using PhCH 3 as a solvent/substrate good yields, together with interesting selectivity toward the formation of PhCH 2 Br, are obtained with both metal ions. Recycling of the catalytic phase is also possible. Usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Furthermore, the monoperoxido vanadium complex was more reactive than the diperoxido complex toward the oxybromination of alkenes and alkynes; [27,32] recently good results have also been obtained in the benzylic bromination of toluene. [28] At higher reaction temperature (Entry 7), quantitative conversion of the substrate was observed, and the bromination reaction proceeded faster. However, it was accompanied by the oxidation of the substrate with hydrogen peroxide, which also led to the formation of 2-isopropyl-5-methyl-1,4-benzoquinone as byproduct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the monoperoxido vanadium complex was more reactive than the diperoxido complex toward the oxybromination of alkenes and alkynes; [27,32] recently good results have also been obtained in the benzylic bromination of toluene. [28] At higher reaction temperature (Entry 7), quantitative conversion of the substrate was observed, and the bromination reaction proceeded faster. However, it was accompanied by the oxidation of the substrate with hydrogen peroxide, which also led to the formation of 2-isopropyl-5-methyl-1,4-benzoquinone as byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the oxidative bromination of toluene has been performed with the system described above, achieving the functionalization at the benzylic position. [28] The reaction has also been carried out without solvent, thus avoiding the use of chlorinated co-solvents to obtain products derived from the electrophilic aromatic substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, we have been involved in the study of the oxidative bromination of toluene, using NH 4 VO 3 as the catalyst [27]. Next to bromination products at the benzylic position, we found that, changing parameters, also benzaldehyde formation could be observed.…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, the reactivity of vanadium-peroxo and molybdenum-diperoxo complexes is definitely superior than that of H 2 O 2 in oxidation reactions, therefore the oxidation of different alkanes, alkenes, alcohols, aromatic substrates, sulphides, as well as oxybromination reactions were successfully achieved with such catalytic systems [41][42][43][44]. Literature reports suggest that vanadate/peroxide oxidation system acts following substrate specifics in radical or ionic modes [38,41,45,46].…”
Section: Catalytic Systemsmentioning
confidence: 99%